The Impact of the Covid-19 Pandemic on Tourism Sector in Indonesia Using a Structural Path Analysis Based on Inter-Regional Input-Output Matrix - Habi Cahya Kumara; Dedy Prastyo; Santi Puteri Rahayu (Universitas Sebelas Maret, 2021)
At the end of 2019 the world was shocked by the new emerging infectious disease in China; the Coronavirus disease (Covid-19). This outbreak is spreading fast and has infected almost all countries including Indonesia, the WHO has designated Covid-19 as a pandemic. The Indonesian government issued a policy of limiting community activities in an effort to break the spread of the virus. This restriction resulted in a significant reduction in economic demand. Based on the release of economic growth data by BPS, Indonesia experienced a recession in the third quarter of 2020 with the transportation and tourism sectors being the sectors most affected by this pandemic. This study will analyze the impact of the Covid-19 pandemic in Indonesia on the tourism sector and its relationship with other sectors using Backward Linkage, Forward Linkage, Multiplier Effects, and Structural Path Analysis (SPA) methods on Indonesia's Inter-Regional Input Output (IRIO) data. According to the results of the analysis up to October 2020, Indonesia lost potential income in the tourism sector by 165.97 trillion rupiah. The hotel and restaurant sector has the largest impact on the formation of output by -99.09 trillion rupiah. The decline in output of hotel and restaurant sector gave a high multiplier impact on the food and beverage sector by -17.9 trillion rupiah and trade sector by -10.7 trillion rupiah. Regionally, the province of Bali and DI Yogyakarta became the provinces with the biggest impact from the decline in tourism due to the composition of the tourism sector in it’s regional economy is equal to 34,8% and 26,5%.